ESCMID guidelines for the management of the infection control measures to reduce transmission of multidrug‐resistant Gram‐negative bacteria in hospitalized patients. (January 2014) - Tacconelli, E.; Cataldo, M. A.; Dancer, S. J.; De Angelis, G.; Falcone, M.; Frank, U.; Kahlmeter, G.; Pan, A.; Petrosillo, N.; Rodríguez‐Baño, J.; Singh, N.; Venditti, M.; et al.
Abstract: Healthcare‐associated infections due to multidrug‐resistant Gram‐negative bacteria (MDR‐GNB) are a leading cause of morbidity and mortality worldwide. These evidence‐based guidelines have been produced after a systematic review of published studies on infection prevention and control interventions aimed at reducing the transmission of MDR‐GNB. The recommendations are stratified by type of infection prevention and control intervention and species of MDR‐GNB and are presented in the form of 'basic' practices, recommended for all acute care facilities, and 'additional special approaches' to be considered when there is still clinical and/or epidemiological and/or molecular evidence of ongoing transmission, despite the application of the basic measures. The level of evidence for and strength of each recommendation, were defined according to the GRADE approach.